Handbook on Poverty Statistics : Concepts Methods and Policy Use. &#x000A - United Nations; United Nations Statistics Division (Geneva : United Nations, 2005)
The handbook provides a comprehensive review of the current practices of poverty measurement worldwide and sketches a road to improving country practices while achieving greater comparability within and across countries. It is hoped that the book will serve as the basis for formulating national, regional and international statistical programs to strengthen the capacity in member countries to collect and analyze data.
Special Project on Poverty Statistics. United Nations Statistics Division, December, 2005.
oif 19/06/14
Loan
Keywords: Poverty -- Statistics